SENIOR HIGH SCHOOL STUDENTS’ PERCEPTIONS ON THE ROLE OF GOOGLE TRANSLATE IN ENGLISH LEARNING AID - Zukhruf Umul Pratiwi (Graduate Program, University of Islam Malang, 2021)
Google Translate (GT) as one of the items given by Google has become a well known interpretation device for language understudies. As English thought to be an unknown dialect in Indonesia, numerous Indonesian understudies use GT to help them in learning English. This device will in general assist the understudies with getting the interpretation rapidly and without any problem. Accordingly, this examination was utilized to research senior high school students’ perceptions on the role of Google Translate in English learning aid. This investigation utilizes a review strategy. The review was picked in light of the fact that this examination thought about the time and pandemic circumstance. To gather the data by utilizing a survey and to circle back to interviews for additional top to bottom information. The inclusion of the two information from the study and those from the meeting is to acquire more reliable data concerning understudies' discernment toward Google Translate in English learning aid. This research was proposed to respond to these inquiries: (1). What are the view of senior high school students about the role of Google Translate in English learning aid? (2). How is the role of Google Translate in higher student competence, middle student competence, and lower student competence? Moreover, this investigation followed up the aftereffect of the survey by meeting 3 out of those 18 members, middle student competence, and lower student competence. To gather the information poll was disseminate use Google form media with numerous decision things, and Whatsapp media to gather talk with information. The discoveries uncover that the vast majority of the understudies in 11th Bahasa MA AL-ITTIHAD concurred that Google Translate was easy to use, it was helpful, and gave advantages for their English learning aid for all levels.And students agreed that Google Translate could help them in learning English and they have willing in using Google Translate as an alternative way to learn English because GT can be used not only for translating but also be used to learn sounds or pronunciation. GT is often used to help the process of translating from English to Indonesian. Students must understand the system working of GT is word by word, so they can defeat their shortcomings and produce an exact interpretation they should address by focusing on language structure and word decision.Keywords: Perception, Google Translate, Learning Aid